PENGARUH PENERAPAN STRATEGI BELAJAR PQ4R TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN CERITA ANAK DI SEKOLAH DASAR - Putra, Rizky Alam; Halidjah, Siti; Mastar, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze whether there is influence of application of learning strategy of preview, question, read, reflect, recite, review (PQ4R) to reading comprehension skill of VA class student of Pontianak City elementary school. From the results of observation, it is known that in reading comprehension learning, 12 out of 24 students still find it difficult to deduce the results of the text they read. The method used is experimental method, while the research used pre-experimental design with one-group pretest-posttest design. Population and sample in this research is all student of class of VA Primary School of State 05 Pontianak City of academic year 2017/2018 amounted to 24 student. Data collection techniques used in this study are the technique of direct observation and measurement techniques. The research instrument used was observation sheet and reading skill test. Based on result of data analysis from mean value pre-test 57,79 and average post-test 70,46. T test result obtained  = 5%, with db = 23 is 2.069. Because  (18,23)>  (2,069), so alternative hypothesis (Ha) accepted, it can be concluded that there is influence of applying learning strategy of preview, question, read, reflect, recite, review (PQ4R) class VA Elementary School 05 Pontianak City.  Keywords: Reading comprehension skills, Learning strategy PQ4R